2022
DOI: 10.3389/fphar.2022.858139
|View full text |Cite|
|
Sign up to set email alerts
|

Real-World Prescription Patterns For Patients With Young-Onset Parkinson’s Disease in China: A Trend Analysis From 2014 to 2019

Abstract: Introduction Pharmacotherapy is one of the main treatments for patients with young-onset Parkinson’s disease (YOPD). Although numerous studies on the treatment of YOPD have been published, the real-world prescription patterns of these populations remain unclear in China.Methods A national comprehensive evaluation was performed to reveal the pharmacological treatment patterns in Chinese patients with Parkinson’s disease from 1 January 2014 to 31 December 2019, with patients aged 21–50 years classified as having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In studies from India, 5,52,53 New Zealand, 54 and Japan, 55 anticholinergics are prescribed to 24–40% of patients with PD 56 . Despite the frequent use in large populations of PD in this as well as other regions of the world, 3‐8,57 we found no LED conversion formulae for anticholinergics, such as trihexyphenidyl, in our systematic review.Therefore, we developed an LED conversion for this drug class taking the two following studies into consideration: First, a Cochrane systematic review of nine RCTs of anticholinergic drugs in PD reported that anticholinergics are more effective than placebo as monotherapy or as an adjunct to other antiparkinsonian drugs 58 . Second, a head‐to‐head study compared the clinical efficacy of single‐dose administrations of 4 mg trihexyphenidyl and 200/50 mg levodopa/carbidopa on total motor examination (UPDRS‐III) 59 .…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…In studies from India, 5,52,53 New Zealand, 54 and Japan, 55 anticholinergics are prescribed to 24–40% of patients with PD 56 . Despite the frequent use in large populations of PD in this as well as other regions of the world, 3‐8,57 we found no LED conversion formulae for anticholinergics, such as trihexyphenidyl, in our systematic review.Therefore, we developed an LED conversion for this drug class taking the two following studies into consideration: First, a Cochrane systematic review of nine RCTs of anticholinergic drugs in PD reported that anticholinergics are more effective than placebo as monotherapy or as an adjunct to other antiparkinsonian drugs 58 . Second, a head‐to‐head study compared the clinical efficacy of single‐dose administrations of 4 mg trihexyphenidyl and 200/50 mg levodopa/carbidopa on total motor examination (UPDRS‐III) 59 .…”
Section: Resultsmentioning
confidence: 68%
“…In studies from India, 5,52,53 New Zealand, 54 and Japan, 55 anticholinergics are prescribed to 24–40% of patients with PD 56 . Despite the frequent use in large populations of PD in this as well as other regions of the world, 3‐8,57 we found no LED conversion formulae for anticholinergics, such as trihexyphenidyl, in our systematic review.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Besides, trihexyphenidyl, an anticholinergic anti-PD drug, was also a commonly used PIM, though it should be avoided in patients aged 60 and above for its possible cognitive impairment, as suggested by both the AGS Beers criteria and the Chinese guidelines for PD management [ 9 , 32 , 33 ]. Nevertheless, 16.5% of older adults with PD used trihexyphenidyl in our study, which was even higher than that among patients aged under 50 and with young-onset PD in China (14%) [ 34 ].…”
Section: Discussionmentioning
confidence: 69%